Association between cam-type femoroacetabular impingement and osteitis pubis in non-athletic population on magnetic resonance imaging - Akgün, Ayşe Serap; Ağırman, Mehmet (BMC, 2019)
Background Osteitis pubis (OP) is a common source of groin and extra-articular hip pain and is associated with intra-articular hip pathology. In this study, we aimed to determine the prevalence of osteitis pubis on magnetic resonance imaging (MRI) in non-athletic patients with cam-type femoroacetabular impingement (FAI). Methods This retrospective cross-sectional study included 178 subjects: 90 patients with cam-type FAI diagnosed by MRI and 88 subjects used as a control group. Additionally, their MRI data were analyzed for the characteristics of osteitis pubis, with severity graded from minimal to severe on a four-point scale. Results A total of 98 patients and 88 controls were studied. Seventy-two males (80%) and 18 females (20%) were the patient group, whereas 71 males (80.68%) and 17 females (19.32%) were the control group. The mean alpha angle of the patients with FAI was 65.8 +/- 3.3 degrees in the right side and 66.2 +/- 3.2 degrees in the left side, whereas in the control group, it was 47 +/- 5.6 degrees in the right side and 47.8 +/- 5.2 degrees in the left side. Alpha angle measurements were significantly higher in the patient group than the control group (p < 0.001). A statistically significant increase in the prevalence of osteitis pubis was found in patients with cam-type FAI (45.56%) compared to control subjects (5.68%) (p < 0.001). Conclusions This study demonstrated that the frequency of osteitis pubis was increased in non-athletic patients with FAI syndrome. Further studies are required to determine whether these findings reflect the clinical symptoms in patients with hip pain.
Keywords: Femoroacetabular Impingement; Osteitis Pubis; Magnetic Resonance Imaging